Explanations of the Polite Hortative form -(i)mash-ō in Current Resources and a Proposition of a Morphological Approach - Rozwadowski, Przemysław Damian (Silva Iaponicarum, 2024)
The aim of this paper is to demonstrate how the description of Japanese grammar is explained in current resources and to present another, more systemic, morphological approach. It will be achieved by examining explanations of the basic level grammatical unit -(i)mash-ō which can be roughly translated as ‘let’s’. At the beginning the crucial characteristics of present description are portrayed. After showing the basics of the traditional, syllabary description, examples of -(i)mash-ō explanations derived from textbooks are given. Then the author analyzes -(i)mash-ō in accordance with its morphological properties. This approach argues that it is in fact a compound built of smaller units each bearing a separate meaning. Afterwards they can be divided and located in different grammatical dimensions. The morphological segmentation of grammatical units can be used in many other occurrences. This would make paradigmatical descriptions of inflection related phenomena more possible.